Planning – A Risky Business? - McInerney, Amy (Victoria University of Wellington Law Review, 2017)
Since the introduction of performance-based planning, Queensland's planning law framework has been repeatedly amended in response to complaints of complexity. This article traces Queensland's law reform journey and focuses on the issue of complexity in the context of planning schemes. The causes of complexity are diverse and to some extent remain unresolved. An issue that warrants more attention is the concept of "risk" in the context of planning (and particularly planning schemes). Risk-based approaches to regulation have been increasingly regarded as an effective way to manage risk and uncertainty. This article asks questions about risk concepts in planning and argues in favour of further research around a risk-based approach to planning scheme preparation.